A geoelectric study of aquifers in the Essaouira coastal region, Morocco. (November 2021) - Ouzerbane, Zakaria; Aïfa, Tahar; El Hmaidi, Abdellah; Essahlaoui, Ali; Najine, Abdessamad
Abstract: A geophysical study carried out in the framework of the water resources recognition within the Essaouira coastal area (Morocco) enabled to outline the spatial distribution of the Plio-Pleistocene and Cretaceous formations. It helped to determine the thickness and extension of the main aquifer used for irrigation purpose. The overall aim of this study is to highlight the hydrogeological structures of Essaouira Basin. A total of 45 vertical electrical soundings (VES) were measured using linear Schlumberger array configuration with a maximum half-length (AB/2) of 1000 m along eight sections of 126 km total length. The number of soundings constituting the eight VES profiles depends on the topography and the obstacles encountered. The VES data were processed and interpreted. According to the thematic maps of the study area, the results indicate the existence of three types of VES with apparent resistivity values ranging from 44 to 320 Ω m. In relationship with wells and mechanical drillings existing in the area, the analysis of the results obtained made it possible to derive from the quantitative and qualitative maps the different apparent resistivity variations of the aquifer and aquiclude geological layers. The careful examination of these maps shows that the region around the Qsob River is of interest from a hydrogeological point of view. It is represented by a significant thick layer given the large extension of the resistive Plio-Pleistocene and Cretaceous formations. Geophysical studies show that this region is partially protected from marine intrusion given its location between Tidzi Diapir and hidden diapir from Essaouira which little plays the role of barrier. It is crossed by the Qsob River which lends itself as the main source of both these layers. The electrical discontinuities emerging from the superposition of the different maps, E-W, NE-SW and NNE-SSW oriented, are abundant and dense in the north Haha region (Qsob River). Generally, the salt water circulates along these discontinuities from West to North and Northeast which explains the abundance of low apparent resistivity values recorded northeastwards. This geophysical reconnaissance is the most important for water supply of this area affected by increasingly long periods of drought. Highlights: Vertical Electrical Soundings carried out on 45 sites in the Essaouira coastal area, enabled to outline the spatial subsurface distribution of Plio-Pleistocene and Cretaceous aquifers. Aquifers exhibit apparent resistivity and thickness values from 44 to 320 Ω m and from 15 to 56 m, respectively. Qsob River area shows a thick layer of resistive Plio-Pleistocene and Cretaceous formations. Isopach and isobath maps of the aquifers confirm their spatial distribution regarding saltwater intrusions. Major faulting system, NNE-SSW, NNW-SSE and E-W oriented, accommodating small grabens, controls the aquifers.